EMU and the adjustment to asymmetric shocks: the case of Italy - Gianni Amisano; Nicola Giammarioli; Livio Stracca (European Central Bank (ECB), 2009)
In this paper we address the question on whether EMU has amplified or dampened intra euro area divergencies, by looking at a time-varying VAR model of Italy's relative performance compared with the rest of the euro area, spanning from 1976 to 2009. Our main result is that EMU does not appear to have materially changed the transmission mechanism of idiosyncratic demand and cost push shocks, but has removed an importance source of relative performance variability given by idiosyncratic monetary shocks. The net effect of EMU, therefore, has been to reduce the relative performance variability. The conclusions that we reach could be usefully tested on other countries.
Keywords: E31; E32; E42; 330; adjustment; EMU; Italy; relative economic performance; shocks; Eurozone; Geldpolitische Transmission; VAR-Modell; Wirtschaftswachstum; Vergleich; Italien; EU-Staaten